Non-Stationarity in Multisensory Neurons in the Superior Colliculus - Perrault, Thomas J.; Stein, Barry E.; Rowland, Benjamin A. (Frontiers in Psychology, 2011)
The superior colliculus (SC) integrates information from multiple sensory modalities to facilitate the detection and localization of salient events. The efficacy of “multisensory integration” is traditionally measured by comparing the magnitude of the response elicited by a cross-modal stimulus to the responses elicited by its modality-specific component stimuli, and because there is an element of randomness in the system, these calculations are made using response values averaged over multiple stimulus presentations in an experiment. Recent evidence suggests that multisensory integration in the SC is highly plastic and these neurons adapt to specific anomalous stimulus configurations. This raises the question whether such adaptation occurs during an experiment with traditional stimulus configurations; that is, whether the state of the neuron and its integrative principles are the same at the beginning and end of the experiment, or whether they are altered as a consequence of exposure to the testing stimuli even when they are pseudo-randomly interleaved. We find that unisensory and multisensory responses do change during an experiment, and these changes are predictable. Responses that are initially weak tend to potentiate, responses that are initially strong tend to habituate, and the efficacy of multisensory integration waxes or wanes accordingly during the experiment as predicted by the “principle of inverse effectiveness”. These changes are presumed to reflect two competing mechanisms in the SC: potentiation reflecting increases in the expectation that a stimulus will occur at a given location, habituation reflecting decreases in stimulus novelty. These findings indicate plasticity in multisensory integration that allows animals to adapt to rapidly changing environmental events while suggesting important caveats in the interpretation of experimental data: the neuron studied at the beginning of an experiment is not the same at the end of it.